Rate Constants of Electrochemical Reactions in a Lithium-Sulfur Cell Determined by Operando X-ray Absorption Spectroscopy. Issue 14 (1st January 2018) - Wang, Dunyang Rita; Shah, Deep B.; Maslyn, Jacqueline A.; Loo, Whitney S.; Wujcik, Kevin H.; Nelson, Erik J.; Latimer, Matthew J.; Feng, Jun; Prendergast, David; Pascal, Tod A.; Balsara, Nitash P.
Abstract : The reduction of sulfur during discharge in a lithium-sulfur (Li-S) cell is known to occur in a series of reaction steps that involve lithium polysulfide intermediates. We present an operando study of the discharge of a solid-state Li-S cell using X-ray absorption spectroscopy (XAS). In theory, the average chain length of the polysulfides, xavg, cell, at a given depth of discharge is determined by the number of electrons delivered to the sulfur cathode. The dependence of xavg, cell measured by XAS on the depth of discharge is in excellent agreement with theoretical predictions. XAS is also used to track the formation of Li2 S, the final discharge product, as a function of depth of discharge. The XAS measurements were used to estimate rate constants of a series of simple reactions commonly accepted in literature.